RESPON TANAMAN TERONG UNGU (Solanum melongena L.) AKIBAT PEMBERIAN PUPUK ORGANIK CAIR MOL DAUN GAMAL (Gliricidia sepium (Jacq.) Kunth ex Walp.) TERHADAP PERTUMBUHAN DAN HASIL - Busroni Asnawi; Rostian Nafery; Ayu Puspita Sari (JURNAL TRIAGRO, 2018)
Response of Purple Eggplant  (Solanum melongena L.) Due to Organic Liquid Fertilization MOL Gamal Leaf (Gliricidia sepium (Jacq.) Kunth ex Walp.) on the Growth and Yield.  This research aims to determine the response of purple eggplant (Solanum melongena L.) due to the application of liquid organic fertilizer MOL gamal leaf (Gliricidia sepium (Jacq.) Kunth ex Walp) on the growth and yield. This research was conducted in Kedondong Raye village chief, Banyuasin III sub-district, Banyuasin district, South Sumatera province, from April 2017 until August 2017.nThe research design used was experimental method using Randomized Block Design (RBD) with 6 treatments and 4 replications. The number of plants studied in the experimental unit is 10 plant samples. The treatments studied were concentration MOL gamal leaf that is P0 = 0%, P1 = 10%, P2 = 20%, P3 = 30%, P4 = 40%, P5 = 50%. The observed variables were plant height (cm), number of branches, number of flowers in each plant, number of fruit in each plant (fruit), fruit weight in each plant (g), fruit weight of plant (g). Based on the results of the study concluded that: 1). Giving of MOL leaf gamal has not affected the growth of purple eggplant plant (Solanum melongena L.) but good effect on the results.  2). The average yield of purple eggplant plant is height of 42.06 cm at the age of 77 day after plant, the branch number is 2.55 at the age of 80 day after plant, the number of flowers in each plant is 11,10 pieces , and the number of fruit in each plant on much as 2.71 fruit.  3). Giving of MOL of Gamal leaf at treatment of P2 (20%) showed good result that is average fruit weight in each plant equal to 219.03 g and weight of fruit in each plot on average equal to 4027.75 g.